Еврооблигации в процессе развития европейской интеграции - Белоцерковский, Александр Борисович (НТУ "ХПИ", 2015)
В данной статье в контексте процесса европейской интеграции рассматриваются различные актуальные вопросы, касающиеся зарождения и развития еврооблигаций. Особое внимание уделено роли и значению суверенных еврооблигаций стран еврозоны как индикатора состояния экономики в период глобального финансово-экономического кризиса.

Eurobonds in the context of the European integration process addresses various topical issues relating to the origin and development of Eurobonds. Particular attention is paid to the role and value of sovereign bonds of the eurozone countries during the global financial crisis, as an indicator of the state of the economy. Sovereign Eurobonds are an important indicator of the market process of European integration and the economy in the eurozone, which, in particular, clearly evident during the global financial crisis. In addition, the Eurobond market to date and is a very serious problem compliance with a proper balance in the borrowing through the issuance of government bonds with the indicators of real economic growth in the EU.
Eurobonds in the process of European integration
Keywords: финансово-экономический кризис; еврозона; Европейский центральный банк; ЕЦБ; economic crisis; euroarea